Solutions of the Schrodinger equation of the shifted screened Kratzer potential and its thermodynamic functions using the extended Nikiforov–Uvarov method - Ibrahim, Nuhu; Okorie, Uduakobong Sunday; Sulaiman, Nidhal; Rampho, Gaotsiwe Joel; Ramantswana, Morris (Frontiers in Physics, 2022)
By employing the extended Nikiforov-Uvarov (ENU) method, we solved the radial Schrodinger equation with the shifted screened Kratzer potential model. The analytical expression of the energy eigenvalues and numerical results were determined for some selected diatomic molecule systems. Variations of the energy eigenvalues obtained with potential parameters and quantum numbers were discussed graphically. Also, variations of different thermodynamic properties with temperature and maximum vibration quantum number were discussed extensively. Our results correspond to the results obtained in literatures. The shifting parameters contribute great effect to the energy results obtained. It has also been established that there exist a critical temperature at specific entropy values for the selected diatomic molecule systems.